Facing Demographic Challenges: Marketing Strategies for Retaining and Attracting Students at SMKS Muhammadiyah Tumijajar - Ratna Dewi Setyowati; Siti Patimah; Subandi Subandi; Deden Makbuloh (Universitas Muhammadiyah Enrekang, 2023)
Education is a key aspect in the development of a country. Vocational High Schools (SMK) have an important role in providing quality vocational education to the younger generation. However, like many other educational institutions, SMKS Muhammadiyah Tumijajar is also faced with significant challenges, one of which is demographic challenges. Demographic challenges refer to changes in the demographic structure of a population, which can impact social institutions, including educational institutions . This research aims to understand the demographic challenges faced by SMKS Muhammadiyah Tumijajar, explore alternative solutions that can be implemented, and formulate the most suitable solution for this institution. The results of the research show that the demographic challenges faced by the Muhammadiyah Tumijajar Vocational School are a decrease in the number of students in several skill concentrations, especially in the field of culinary arts , migration and urbanization of the population, which causes people's desire to study outside areas that are considered better , as well as competition . with other educational institutions. To overcome these challenges, Muhammadiyah Tumijajar Vocational School needs to implement an effective and sustainable marketing strategy. This strategy must be able to increase student interest in choosing a concentration of expertise at SMKS Muhammadiyah Tumijajar , retain existing students , and increase the competitiveness of SMKS Muhammadiyah Tumijajar among other educational institutions. Based on the research results, an effective marketing strategy for Muhammadiyah Tumijajar Vocational School is improving the quality of education and learning , carrying out effective promotions and branding , and building collaboration with strategic partners. It is hoped that the implementation of this marketing strategy can help Muhammadiyah Tumijajar Vocational School to remain relevant and competitive in the future.